2018
DOI: 10.4314/bajopas.v10i1.30s
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological evaluation of shelflife indices of fermented African locust bean cake stored under different preservative treatments

Abstract: This study was carried out on the preservation of fermented Parkia bigl from Local Producers and laboratory produced. The local and fermented laboratory controlled samples were treated with 0.5ml of freshly prepared ginger extract. Another set of control was left untreated. The samples were stored at ambient temperature for 30 and 120 days. Contaminant isolates were identified from locally produced, laboratory treated and untreated (Control) using standard procedure. The analysis consisted of Aerob Anaerobic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…A significant decrease in the TVC, TCC and FC was observed with an increase in the botanical concentration. Accordingly, Rabi et al (2017), who reported a decrease in microbial composition of fermented African locust bean when powdered ginger was added as preservative corroborate the finding of the current investigation. The TVC decreased from 8.4×10 5 cfu/g to 3.9×10 5 cfu/g, the TCC decreased from 6.2×10 5 cfu/g to 2.9×10 5 cfu/g and the FC decreased from 4.4x10 3 cfu/g to 1.2×10 3 cfu/g.…”
Section: Effect Of Storage Parameters On the Microbial Composition Of The Stored Productssupporting
confidence: 91%
See 1 more Smart Citation
“…A significant decrease in the TVC, TCC and FC was observed with an increase in the botanical concentration. Accordingly, Rabi et al (2017), who reported a decrease in microbial composition of fermented African locust bean when powdered ginger was added as preservative corroborate the finding of the current investigation. The TVC decreased from 8.4×10 5 cfu/g to 3.9×10 5 cfu/g, the TCC decreased from 6.2×10 5 cfu/g to 2.9×10 5 cfu/g and the FC decreased from 4.4x10 3 cfu/g to 1.2×10 3 cfu/g.…”
Section: Effect Of Storage Parameters On the Microbial Composition Of The Stored Productssupporting
confidence: 91%
“…The addition of the botanical concentration into the samples of the products might partly be responsible for the decrease in the values of the TVC, TCC and FC with an increase in the storage period. The research effort of Rabi et al (2017) who reported a decrease in the microbial composition of fermented African locust bean as a result of the powdered ginger applied has also given credence to the current investigation. This show that the storage period and the botanical used had a greater influence on the microbial counts of the stored Irvingia gabonensis powder.…”
Section: Effect Of Storage Parameters On the Microbial Composition Of The Stored Productssupporting
confidence: 61%